The OsIME4 gene identified as a key to meiosis initiation by RNA in situ hybridization. (25th June 2021) - Zhou, W.; Li, Z.; Zhang, J.; Mou, B.; Zhou, W.
Abstract: The formation of asexual seeds in plants holds great promise as a breeding system for one‐line hybrid rice. Entry into meiosis is a key developmental decision in gametogenesis, especially in formation of asexual seeds in plants. Apomeiosis in MeMCs can be achieved by identifying and manipulating meiosis‐specific genes. Using methods based on in situ hybridization and expression analysis, we identified OsIME4 (inducer of meiosis 4) sense and antisense transcripts involved in rice meiosis initiation, similar to initiation of meiosis in budding yeast. Our data suggest that the OsIME4 sense transcript, which encodes a putative mRNA N6‐adenosine methyltransferase, keeps rice cells at mitosis stage through some form of epigenesis (DNA/RNA methylation), and the non‐coding antisense transcript of OsIME4 converts the cell status from mitosis to meiosis by inhibiting expression (transcription and translation) of the sense transcript. We identified that the non‐coding antisense transcript of OsIME4 converts archesporial cell status from mitosis to meiosis by inhibiting expression of the OsIME4 sense transcript in rice. Our results provide novel insights into meiosis initiation in rice and for engineering of apomixis in sexual crops by manipulating the OsIME4 sense and antisense transcripts, which has great promise for producing apomictic rice in the future. Abstract : Antisense transcript of OsIME4 converts the cell status from mitosis to meiosis by inhibiting the expression of sense transcript.